1968
DOI: 10.1126/science.159.3820.1243
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Human Lymphocytes: Inhibition by Homologous Alpha Globulin

Abstract: An alpha globulin fraction prepared from normal human plasma by column chromatography prevents homologous lymphocyte transformation and the stimulation of DNA, and also protein synthesis induced by phytohemagglutinin and specific antigens. These observations support the concept of a normal circulating immunosuppressant factor which prevents lymphoid cell proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
5

Year Published

1969
1969
1986
1986

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(41 citation statements)
references
References 12 publications
1
35
0
5
Order By: Relevance
“…Moreover, normal serum also contains factors that inhibit PHA-stimulated blast transformation and there is evidence that the inhibiting factor in normal serum may be an a, globulin (25). We found that normal serum depressed spontaneous and Con A-stimulated lymphocyte blast transformation in controls but had no effect on lymphocyte cytotoxicity.…”
Section: Resultsmentioning
confidence: 54%
“…Moreover, normal serum also contains factors that inhibit PHA-stimulated blast transformation and there is evidence that the inhibiting factor in normal serum may be an a, globulin (25). We found that normal serum depressed spontaneous and Con A-stimulated lymphocyte blast transformation in controls but had no effect on lymphocyte cytotoxicity.…”
Section: Resultsmentioning
confidence: 54%
“…Cooperband et al (1968) (Heilman and MacFarland, 1966); hepatitis (Paronetto and Popper, 1970); ataxia telangiectasia (MacFarlin and Oppenheim, 1969); secondary syphilis (Levene et al, 1969); chronic candidiasis (Canales et al, 1969); Hodgkin's disease (Trubowitz, Masek and del Rosario, 1966); as well as cancer (Trubowitz et al, 1966;Salk, 1967;and others). With the present highly sensitive and quantitative method of assessing lymphocyte sensitization, the titre of LDF in health and disease can readily be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking activity in the purified fractions resided in molecules presumptively identified as glycoproteins by affinity chromatography on concanavalin A-Sepharose. The cellular immune response of an animal against its growing tumor can be inhibited by various circulating factors, some of which cause a generalized immune nonresponsiveness (1,2) and some of which are tumor specific (3,4). We have taken a particular interest in the specific factors, following the demonstration that sera from animals with growing tumors can specifically prevent immune lymphocytes from killing tumor targets as measured by in vitro cytotoxicity assays (3).…”
mentioning
confidence: 99%